Application of solid lipid nanoparticles preparation in infection caused by antibiotic-resistant bacteria - Prastiwi, Nenes; Ervina; Lesbatta, Kezia (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
Solid lipid nanoparticles (SLN) is a potential alternative method for drug delivery due to its good stability, low toxicity, can be modified and controlled in drug release, as well as can be produced on a large scale. The SLNs are composed of solid lipids stabilized by emulsifiers. The lipids used for SLN are physiological lipids that easily tolerated by the body. These characteristics make SLN as a potential delivery system that can increase the efficiency of an antibiotics preparation. The development of bacterial resistance to antibacterial has become serious health problems in infectious diseases. Solid lipid nanoparticles is a compelling choice as a drug delivery system that can reduce the problem of the bacterial resistance. This review discussed the role of SLN as a drug carrier system which includes the characteristics and structure of SLN, its pharmacokinetic properties, bacterial resistance mechanism, and SLN mechanism in reducing bacterial resistance.